Folktales of Bihar: A Study of the Animal Characters - Mahato, Ashis; Singh, Nishant (International Journal of Language and Literary Studies, 2024)
Cultural elements in folktales can manifest through idiomatic expressions, metaphors, proverbs, or references to specific historical events or figures. Each of these elements holds significant cultural value, enriching the story and providing insights into the community's collective experiences and values. In India, folktales are cherished by millions for their entertainment and aesthetic value. These tales are typically passed down orally from one generation to the next, and in more recent times, they may also be found in written form. Folktales from different regions reflect the thoughts, traditions, and culture of their people, providing both entertainment and insight into their past and present customs. Bihar is one of the most important states of India, located in the eastern region of the country, and has a rich tradition of folk culture. We often observe the representation of animal characters in folktales. In the context of the folktales of Bihar, we can also observe the depiction of different types of animal beings. The purpose of this study is to analyze how the animals are represented in the context of folktales of Bihar. To undertake this study, we need to utilize the descriptive analysis approach. To undertake this study, we need to utilize the descriptive analysis approach.